2009
DOI: 10.1103/physreve.79.041920
|View full text |Cite
|
Sign up to set email alerts
|

Levels of complexity in scale-invariant neural signals

Abstract: Many physical and physiological signals exhibit complex scale-invariant features characterized by 1/f scaling and long-range power-law correlations, suggesting a possibly common control mechanism. Specifically, it has been suggested that dynamical processes influenced by inputs and feedback on multiple time scales may be sufficient to give rise to 1/f scaling and scale invariance. Two examples of physiologic signals that are the output of hierarchical, multi-scale physiologic systems under neural control are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(107 citation statements)
references
References 107 publications
(168 reference statements)
2
104
0
Order By: Relevance
“…Many different aspects of gait could be examined with a dynamical approach using the techniques described as well as a long list of other analysis methods. 38,53,74,152 Hopefully, the present review and update will motivate additional studies and analyses of gait in PD. The results of this update demonstrate that models that attempt to simulate and mimic the changes in gait in PD should also consider the changes in the fractal scaling and the effects of different interventions on multiple gait characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different aspects of gait could be examined with a dynamical approach using the techniques described as well as a long list of other analysis methods. 38,53,74,152 Hopefully, the present review and update will motivate additional studies and analyses of gait in PD. The results of this update demonstrate that models that attempt to simulate and mimic the changes in gait in PD should also consider the changes in the fractal scaling and the effects of different interventions on multiple gait characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, DFA scaling of the stride time is relatively independent of the data collection method. Ivanov et al 74 recently reported that DFA derived scaling indices of gait obtained using an accelerometer when healthy adults walk on a very long straight path are similar to those of healthy subjects who walked on an oval track while wearing footswitches. 79 Similar scaling values were found by West and Griffin 109 even though another experimental method was used ͑i.e., timing based on knee angles͒, the walking track was a large square path, and the analytical approach used was different.…”
Section: B Assessment Of Gait Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Right panel shows lower beta power across time at the parieto-occipital cluster (8 electrodes) in standard trials. (C) Theta frequency band [4][5][6][7][8] parametric paired t-test maps comparing moderate-to-high intensity and light intensity exercise in target 2 trials (red squares). Right panel shows theta power across time at the globally-localized cluster (7 electrodes) in target 2 trials.…”
Section: Cc-by-nc-nd 40 International Licensementioning
confidence: 99%
“…A representation that relates to time versus frequency information of the signal can be achieved using wavelets; this works well on nonstationary data (de Chazal et al, 2000;Minami et al, 1999;Romero & Serrano, 2001, Sarkaleh & Shahbahrami, 2012. Some algorithms have utilized heartbeat temporal intervals (Alexakis et al, 2003), morphological features (de Chazal et al, 2004), frequency domain features, and multi-fractal analysis (Ivanov et al, 2009). In order to best classify the various types of ECG signals, algorithms in biomedical signal processing require appropriate classifiers.…”
Section: Introductionmentioning
confidence: 99%